Registering Underground Rights: Evaluating Deed Standards and Evidence Post-GR 18/2021 - Maichal Andersen Tampoma; Sunardi Sunardi (Fakultas Syariah INSURI Ponorogo, 2026)
Legal certainty regarding the registration of underground space rights remains a critical challenge in Palu City. This issue stems from unclear evidentiary proof of ownership, a lack of standardized authentic deeds, and the absence of an optimal three-dimensional (3D) land administration system. This study analyzes the standard of deeds that Notaries must prepare for agreements granting underground space rights to ensure legal certainty for all parties. Using a normative legal method with statutory and secondary approaches, the study evaluates the formal legal aspects and official authority outlined in Government Regulation Number 18 of 2021. The results indicate that while this regulation significantly advances Indonesian agrarian law by recognizing underground space as a new legal object, its practical implementation faces severe normative and technical obstacles—particularly in 3D mapping and the formulation of standardized deeds. Consequently, this study concludes that establishing explicit standards for authentic Notarial deeds and developing a robust 3D land registration system are urgent prerequisites for achieving true legal certainty.